Strategic Scarcity Message in Live Commerce: Driving Impulsive Buying through Perceived Value and FOMO - Zaky Mubarak; Agus David Ramdansyah; Yanto Azie Setya (CV. RADJA PUBLIKA, 2026)
Addressing Indonesia’s live commerce “conversion paradox,” where livestream viewership increased from 71% to 86% while purchase rates remained stagnant at 56%, this study examines the inconsistent effectiveness of scarcity messages in stimulating impulsive buying behavior. Drawing upon the Stimulus–Organism–Response (S-O-R) framework, the study investigates whether scarcity messages influence impulsive purchases through the dual mediating roles of Fear of Missing Out (FOMO) as an emotional response and Perceived Value as a cognitive evaluation. A quantitative research design was employed using an online survey of 538 Shopee Live users across Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The findings reveal that scarcity messages do not exert a significant direct effect on impulsive buying behavior. However, scarcity messages significantly enhance both FOMO and Perceived Value. While FOMO significantly mediates the relationship between scarcity messages and impulsive buying, Perceived Value does not demonstrate a significant mediating effect. These results indicate that the emotional pathway represented by FOMO is more influential in driving impulsive purchases than the cognitive pathway represented by Perceived Value. This study contributes to the live commerce and consumer behavior literature by extending the application of the S-O-R framework to a nationwide Indonesian context and highlighting the dominant role of emotional mechanisms in shaping impulsive buying behavior. The findings suggest that marketers and livestream sellers should prioritize strategies that create a sense of urgency and fear of missing opportunities, rather than relying solely on communicating functional product benefits, to improve purchase conversion in live commerce environments.